CSR and Environmental Reporting in the Czech Republic and Romania: Country Comparison of Rules and Practices - Irena Jindrichovska; Irina Purcarea (Journal of Accounting and Management Information Systems (JAMIS), 2011)
This paper focuses on the development of corporate social responsibility, with special emphasis on environmental issues in two countries that have recently joined the EU: the Czech Republic and Romania. The article analyses the short tradition of Corporate Social Responsibility reporting in both countries and the current state of development, as well as its future perspectives. The paper also deals with the recent developments of environmental reporting in the Czech Republic and Romania, and plans to introduce some basics of environmental reporting into compulsory reporting statements in the Czech Republic. This is then compared it with country-specific approach in Romania. On the Czech side, the comparison is drawn from two short case studies of the Czech heavy industry sector. Similarly, in Romania, the approach is documented on companies from the energy sector and a major shipyard, representing the approach of Romanian heavy industry sector. We conclude that the standard of CSR and environmental reporting is based on the same principles in both countries, but the particular approaches differ. Non-prescriptive approach to environmental reporting should be adopted in the Czech Republic, similarly to other developed countries. Furthermore, in our opinion, more systematic regulatory approach may be adopted in Romania.
Keywords: Q58; 650; Corporate social responsibility; environmental accounting; sustainable development; Czech Republic; Romania